A Bean‐Like Formation of Germanium Nanoparticles Inside CNTs by the Subsequent Operation of Colloidal Synthesis and Catalytic Chemical Vapor Deposition Methods. Issue 11 (22nd October 2018) - Karatutlu, Ali; Boi, Filippo S.; Wilson, Rory M.; Ersoy, Osman; Ortac, Bulend; Sapelkin, Andrei
Abstract: The first attempts of implanting Ge nanoparticles (Ge NPs) inside iron filled CNTs (IF‐CNTs) by a subsequent use of the bench top colloidal synthesis and chemical vapor deposition (CVD) approach is shown. Ge NPs are colloidally synthesized (with a 3.8 ± 0.6 nm in size) before the deposition. The hybrid Ge NPs/IF‐CNTs structure and morphology are characterized using high‐resolution transmission electron microscopy, scanning electron microscopy, selective area electron diffraction, and X‐ray diffraction studies. After the deposition, Ge NPs appear to be grown in size and to be sprinkled almost homogeneously into the IF‐CNTs similar to a bean‐like deposition. CNTs diameter is also identified to be enlarged drastically when using Ge NPs as a catalyst in CVD compared to the CNTs formation without Ge NPs. In addition, micro‐length rectangular Ge µPs are also found outside the nanotube core. Rietveld analysis shows the presence of γ‐Fe (Fm‐3m), ferromagnetic α‐Fe (Im‐3m), Fe3 C, Ge (Fd‐3m), and multiwall CNTs. The results indicate that Ge NPs and IF‐CNTs demonstrate cocatalytic activity in increasing the respective sizes, which are dramatically larger than those obtained by the conventional approaches. Abstract : A recipe for a junction of Ge/Fe inside a single CNT is demonstrated with a bean‐like deposition of Ge NPs. The results indicate that Ge NPs and IF‐CNTs demonstrate cocatalytic activity in increasing the respective sizes, which are dramatically larger than those obtained by the conventional approaches.